Recruitment and retention of STEM teachers through the Noyce Scholarship: A longitudinal mixed methods study. (July 2021) - Whitfield, Jennifer; Banerjee, Manjari; Waxman, Hersh C.; Scott, Timothy P.; Capraro, Mary Margaret
Abstract: Staffing high schools with highly qualified mathematics and science teachers continues to be a challenge for schools across the U.S. One way to address this challenge is to offer financial incentives, in the form of scholarships or grants, for high performing college students to become high school mathematics or science teachers. The effects these types of scholarship programs have on the recruitment, retention, and dispositions of teachers is not clear. The current explanatory mixed methods study used longitudinal data from 29 Noyce Scholars from the same university, to investigate the influences the scholarship has on retention and recruitment of STEM teachers in high-need settings. Highlights: Did not heavily influence Scholars' decision to enter the teaching profession. Did not heavily influence Scholars' decision to teach in a high-need school. Helped ensure Scholars work in a high-need school after graduation. The level of influence in retaining beyond commitment was mixed. School administration plays a large role in retaining teachers in high-need schools.